The life, death and diversity of pro-government militias: The fully revised pro-government militias database version 2.0 - Sabine C Carey; Neil J Mitchell; Katrin Paula (Research & Politics)
This article presents version 2.0 of the Pro-Government Militias Database (PGMD). It is increasingly clear that it is untenable to assume a unified security sector, as states often rely on militias to carry out security tasks. The PGMD 2.0 provides new opportunities for studying questions such as when states rely on militias, how they chose among different types and the consequences for stability and peace. We detail how the PGMD 2.0 provides new information on the characteristics, behaviour, life cycle and organization of 504 pro-government militias across the globe between 1981 and 2014.